Acute appendicitis in pregnancy - do we treat correctly, or do we delay unnecessarily - Guňková, Petra; Tulinský, Lubomír; Toman, Daniel; Martínek, Lubomír; Vrtková, Adéla; Špaček, Richard; Šimetka, Ondřej (Ginekologia polska, 2024)
OBJECTIVES: Acute appendicitis is the most common non-gynaecological indication for surgical intervention during pregnancy. The aim of this study was to compare perioperative and postoperative results of surgical treatment of acute appendicitis in the early and late stage of pregnancy. MATERIAL AND METHODS: This is a retrospective study focused on the evaluation of perioperative and postoperative results of appendectomy in pregnancy. The study included all pregnant patients who underwent laparoscopic or open appendectomy at the University Hospital Ostrava during the observed 10-year period (January 2012-December 2021). The patients were divided into two subgroups according to the stage of pregnancy in relation to the expected viability of the foetus (the viability limit was defined as the 23rd week of pregnancy). RESULTS: In the monitored 10-year period, a total of 25 pregnant patients underwent appendectomy. Comparing the two subgroups of patients, there were no statistically significant differences in any of the admission parameters. Laparoscopy was performed in 100% of the patients in the lower stage of pregnancy (< 23 g.w.) and in 61% of the subgroup of patients with more advanced pregnancy (> 23 g.w.); this difference was statistically significant (p = 0.039). Differences in subgroups regarding duration of surgery, risk of revision and 30-day postoperative morbidity were not statistically significant. In the subgroup of patients < 23 g.w., uncomplicated forms of appendicitis predominated (66%), whereas in the subgroup > 23 g.w., complicated forms predominated (69%); this difference was statistically significant (p = 0.026). When comparing the two subgroups of patients, there was a statistically significant difference in the length of hospitalization (p = 0.006). The mortality rate of the group was zero. CONCLUSIONS: The results of the study confirm the fact that advanced pregnancy may be related to complicated forms of appendicitis. Therefore, early appendectomy is still the method of choice. In accordance with the Society of American Gastrointestinal and Endoscopic Surgeons (SAGES) recommendations, laparoscopic approach is preferred in pregnant patients, even in advanced pregnancy.
Keywords: výsledek terapie; Length of Stay; apendicitida; Appendectomy; Postoperative Complications; retrospektivní studie; hospitalizace; Pregnancy; těhotenství; laparoskopie; pooperační komplikace; délka pobytu; Treatment Outcome; akutní nemoc; Acute Disease; lidé; Appendicitis; ženské pohlaví; apendektomie; Humans; Hospitalization; Laparoscopy; Retrospective Studies; Female